Pharmacogenomic Role in Cytochrome P450 Enzymes-Mediated Metabolism for Drug Therapy - Lonah; Zita Arieselia; Jonny Setiawan; Rita Dewi; Maria Dara Novi Handayani; Linawati Hananta (Journal of Urban Health Research, 2023)
The rapid development of genetic science in recent decades has provided opportunities for clinical implementation. In the field of pharmacology, this opens up hope for the use of more targeted drugs with fewer side effects.Genetic variation's influence on pharmacological response has been well-established in practice. Patients' responses to pharmacological therapies can be varied, ranging from positive effects to serious adverse drug reactions (ADRs). Numerous genetic variations have been found to have a major impact on how people react to routinely prescribed medications over time, according to experts. In order to use this genetic information to inform treatment choices, a pharmacogenomic (PGx) profile can be used. PGx works on identifying and validating genomic variations that affect drug response. The generic approach to healthcare has given way to a more individualized and precise treatment paradigm as it has developed. Keywords: Adverse Drug Reactions - Genetic Variants – Pharmacogenomics - Cytochrome P450